Cloud IoT Solutions for Renewable Energy Management in Cities - Verma, Ratnam (Management Analytics and Social Insights, 2025)
As cities worldwide transition to renewable energy sources to combat climate change, the demand for efficient energy management solutions has become paramount. Cloud-based Internet of Things (IoT) solutions provide a reliable method to monitor, control, and enhance renewable energy systems in urban areas. This research examines combining cloud and IoT technologies in renewable energy management, focusing on the difficulties urban energy demand poses, infrastructure constraints, and security threats. A well-defined plan is suggested, which involves utilizing IoT devices for real-time data collection, storing and processing the data in the cloud, and employing advanced analytics techniques for predictive energy management. The framework focuses on scalability, cost-effectiveness, and environmental sustainability. The findings suggest substantial enhancements in energy distribution efficiency and cost savings, highlighting the effectiveness of cloud IoT solutions in smart city energy management. This research highlights the potential of cloud IoT in advancing sustainable urban energy systems, making significant contributions to the broader objectives of smart and sustainable city development.